Data Fusion and Internet of Things (IoT) Approach in Fire Disaster Management - Tajudeen, Adeosun A; Nwiabu, Nuka D (International Journal of Computer Sciences and Engineering, 2019)
This paper presents Data fusion and Internet of things (IoT) approach in Fire Disaster Management. Data fusion techniques in Internet of Things were used for predicting and detecting early fire outbreaks in households and industrial premises. Smoke, temperature and voltage measurement sensory data were used in the system for early fire detection. Action Research Methodology was adopted in carrying out research and UML was used as design tool. The architectural design consists of contextual information such as smoke, room temperature and electricity voltage level as an input. The system was implemented using JavaScript and PHP environment to verify the performance of the proposed system. Dynamic simulations were performed using a real time data obtained from River State Fire Service, Port Harcourt, Rivers State, Nigeria. The performance of the proposed system indicates that data fusion-based system with the use of smoke, temperature and voltage detector is able to detect fires more reliable and highly accurate from the fire detection unit than one sensory data. The results were promising indicating the real state of fire outbreak prediction.